TRANSFORMASI PENDIDIKAN ERA GLOBALISASI: INOVASI KURIKULUM, TEKNOLOGI, PERAN GURU, DAN FOKUS PENGEMBANGAN POTENSI SISWA - Supardi, Supardi; Idris, Ahmad; Nurhayati, Neng; Fauzi, Anis (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to examine aspects of curriculum change, learning methods, use of technology, and the roles of teachers and students. This study is a qualitative study that uses library research methods to examine in depth the concept of innovation and change in the education system. A qualitative approach is chosen to reveal certain social situations by describing reality correctly, formed by words based on relevant data collection and analysis techniques from natural situations. Data and information collection is carried out through a review of various library materials such as books, journals, reports, and documents, with an emphasis on the discovery of theories, laws, propositions, principles, and ideas to analyze and solve the problems studied. The main primary data source in this writing is a journal reference from Putri on the concept of educational innovation, supported by secondary data sources from various other journals and books that discuss the concept and models of educational innovation. Considering that education is the main foundation of the nation's progress, innovation in the era of globalization is crucial. The results show that effective educational innovation must be holistic, sustainable, involve all stakeholders, and be oriented towards improving the quality of learning and developing student potential optimally. Technology plays a crucial role, but its use must be wise, and the development of teacher competencies as agents of change is very important. ABSTRAKPenelitian ini bertujuan mengkaji aspek perubahan kurikulum, metode pembelajaran, penggunaan teknologi, serta peran guru dan siswa. Penelitian ini merupakan studi kualitatif yang menggunakan metode studi kepustakaan (library research) untuk mengkaji secara mendalam konsep inovasi dan perubahan dalam sistem pendidikan. Pendekatan kualitatif dipilih untuk mengungkap situasi sosial tertentu dengan mendeskripsikan kenyataan secara benar, dibentuk oleh kata-kata berdasarkan teknik pengumpulan dan analisis data relevan dari situasi alamiah. Pengumpulan data dan informasi dilakukan melalui telaah berbagai material perpustakaan seperti buku, jurnal, laporan, dan dokumen, dengan penekanan pada penemuan teori, hukum, dalil, prinsip, serta gagasan untuk menganalisis dan memecahkan masalah yang diteliti. Sumber data primer utama dalam penulisan ini adalah rujukan jurnal dari Putri tentang konsep inovasi pendidikan, didukung oleh sumber data sekunder dari berbagai jurnal dan buku lain yang membahas konsep dan model-model inovasi pendidikan. Mengingat pendidikan adalah fondasi utama kemajuan bangsa, inovasi di era globalisasi menjadi krusial. Hasilnya menunjukkan bahwa inovasi pendidikan yang efektif harus bersifat holistik, berkelanjutan, melibatkan seluruh pemangku kepentingan, dan berorientasi pada peningkatan kualitas pembelajaran serta pengembangan potensi siswa secara optimal. Teknologi berperan krusial, namun penggunaannya harus bijak, dan pengembangan kompetensi guru sebagai agen perubahan menjadi sangat penting.